Fatores associados a sintomas de ansiedade em pessoas idosas da Universidade da Maturidade no Polo de Tocantinópolis, TO - Conceição, Emanuela Araújo Da (Universidade Federal do Tocantins, 2024)
The objective of this work was to analyze the factors associated with anxiety symptoms in elderly people at the Universidade da Maturidade do Polo de Tocantinopólis-TO. This is a cross-sectional, descriptive and analytical study. In data collection, a questionnaire with sociodemographic questions, the mini mental state examination, Beck anxiety and depression inventory were applied. Data analysis was carried out using the Statistical Package for The Social (SPSS) software and demonstrated through descriptive and inferential statistics. A significance level of p ≤0.05 and a 95% confidence interval were adopted in all tests. 100 elderly people were evaluated, 60% female and 40% male. The prevalence of anxiety was 21% and the variables that showed an association were: age group (p=0.02), self-perceived health (p = 0.04) and depression (p < 0.001). A high prevalence of anxiety was observed in the researched sample, making it necessary to propose non-pharmacological measures through the practice of physical activity/physical exercise regularly and monitoring of this age group in order to improve the quality and maintenance of physical, mental and emotional health.